Standardization of in vitro nervous tissue culture for honeybee: A high specificity toxicological approach - Azevedo, Patricia [UNESP]; Butolo, Nicole Pavan [UNESP]; de Alencar, Luciano Delmondes; Soares-Lima, Hellen Maria [UNESP]; Sales, Victor Ribeiro; Malaspina, Osmar [UNESP]; Nocelli, Roberta Cornélio Ferreira (Elsevier, 2020)
Bees are important pollinators that help to maintain the biodiversity of wild and cultivated plants. However, the increased and inappropriate use of agrochemicals has caused an imbalance in the populations of these insects visiting flowers for pollen and nectar collection. Therefore, new research methods for understanding the mechanisms of action of pesticides and their impacts on the brains of bees, such as neurotoxicity and cellular changes, in response to different active characteristics and dosages of insecticides are necessary. Thus, with the aim of developing tests with greater specificity at the level of cells or tissues, this study sought to standardize a method for the in vitro culture of the nervous tissue of Apis mellifera. For this purpose, the brains of six foragers bees were transferred to three different insect cell culture media and it supplementation with 10% foetal bovine serum (FBS): Grace, Schneider, Leibovitz, Grace + FBS, Schneider + FBS and Leibovitz + FBS media for each collection time. Nervous tissue was collected after 1, 6, 12 and 24 h of incubation in a humidified CO2 incubator at 32 °C, and histological sections of the organs were analysed. The results showed that Leibovitz medium and Leibovitz medium + serum are potential culture media for the cultivation of nervous tissue, since they resulted in less tissue spacing and tissue disarrangement. Therefore, additional supplements are necessary to obtain an ideal medium for the cultivation of A. mellifera nervous tissue.
Keywords: Insect culture medium; Kenyon cells; Leibovitz's culture medium; Mushroom bodies; Tissue disarrangement; Tissue spacing